Public Support for European Integration in Greece and Italy Between 2015 and 2020 - Nikolas Kouloglou; George N. Georgarakis (Politics and Governance, 2023)
The consecutive crises of the last decade have eroded public support for the EU, especially so among Southern European member states. A long-standing scholarly debate centers around whether it is economic or cultural considerations that drive public support for the EU. However, it is still unclear whether public attitudes toward European integration are driven primarily by economic evaluations or concerns associated with growing immigration flows. To explore this question, we draw on data from the Eurobarometer in Greece and Italy between 2015 and 2020. We find consistent evidence that diffuses public support for the EU and specific support for EU institutions are associated positively with economic evaluations of the European economy and household finances and negatively with opposition to immigration. Our study provides further insights into the dynamics of public support for the EU in the European periphery during critical times.